Investigating rhizosphere dynamics and plant-microbe interactions to alleviate environmental stress - Jameel M. AL-KHAYRI; Tahir KHAN (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Soil acts as a crucial reservoir for both nutrients and microorganisms, hosting a wide range of microbial communities essential for ecosystem health. Particularly noteworthy are the interactions between plants and these microbes in the rhizosphere, as they actively contribute to sustaining plant well-being and fortifying plants against environmental pressures. Challenges, such as drought and salinity, pose significant threats to agricultural output and overall plant development. Therefore, it is imperative to explore the intricate mechanisms of stress responses to develop strategies to bolster plant resilience. Plant growth-promoting rhizobacteria (PGPR) offer a promising avenue for alleviating stress-induced damage in plants. Recent progress in the understanding of drought stress has shed light on the physiological and biochemical reactions within plants, emphasizing the critical role of abscisic acid (ABA) in stress mitigation. Similarly, advancements in research on salinity tolerance have elucidated the functions of ion transporters and stress signaling proteins. PGPRs play a crucial role in enhancing plant stress resilience through various mechanisms, including the regulation of ethylene levels, enhancement of nutrient absorption, and synthesis of hormones and enzymes. Utilizing the synergistic potential of plant-microbial interactions presents a promising strategy for tackling salinity and drought challenges in agriculture. Furthermore, PGPRs are instrumental in mitigating the effects of organic pollutants and heavy metals via mechanisms such as ACC deaminase activity. Innovative approaches, such as constructed wetland systems, leverage plant-microbial interactions to enhance water quality by purging pollutants.